A new species of Sphaeronemoura (Plecoptera: Nemouridae) from Guizhou, China with a revised key to males of this genus - Zhu, Ya-Fei; Du, Yu-Zhou (Zootaxa, 2024)
A new species of the genus Sphaeronemoura, S. fanjingshana Zhu & Du, sp. nov., is described from Guizhou Province of southwestern China. The new species is described using color photography and is compared to other similar species in the genus. We also provide a revised key to the adult males of Sphaeronemoura.